SOME CHARICTERISTIC OF MICROBIAL INDOLE EXTRACTED FROM PATHOGENIC E. COLI IN COMPARABLE WITH STANDARD ONE - Abdulazeez H. Alqaisi; Mouruj A. Al aubydi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Indole molecules as a signal has an important role in bacterial ecosystem, this study was aimed and conducted on the extraction and partial purification of indole from pathogenic E. coli and study several indole characterizations parameters compared with synthetic standard one. A total of 134 urine specimens and other stool 152 specimens were obtained from Al-Ramadi Hospitals, during the period from November / 2018 to March / 2019.The results show the percentage of isolated E. coli from Urinary tract infection was 100 (74.6%)/134, While 152 (100%)/ 152 are isolated from stool. Primary and secondary screening concluded, there are ten isolates are considered as the best in production of indole. The most producible one is selected with indole concentration 165.667 µM/ml. Also, indole production needs several optimal parameters to elevate its production, the study improved that the best pH is 9, temperature is 35 °C, incubation period is 18 hrs. and indole concentration is directly proportional with the amount of tryptophan added. Thin layer chromatography result reveals that no significant difference between extracted indole Rf 0.9 and 0.91 of synthetic standard one. Fourier-Transform-Infrared Spectroscopy, the results show there are some differences in the analysis in some structural positions.